Citizenship Education Learning Strategy in Installing Pancasila Values in Students in Elementary Schools - Munzir, Azzahra (International Journal of Students Education, 2024)
This study aiming for reviewing citizenship education learning strategies in to plant pancasila values in elementary school. Based on studies literature conducted, found some effective learning strategies, such as approach contextual, learning based on problems, and learning active. Approach contextual connect learning with experience daily students, meanwhile learning based on problems and learning active push student for participate in a way direct in understand and apply Pancasila values. In addition, the implementation Pancasila values can done through various method like stories, examples, simulations, games, and education character. The role of teachers is very important in to design creative learning and becoming example for students. Learning based on Pancasila values are expected can to form character positive students and strengthen awareness they as good citizen.